Pengaruh Minat Belajar dan Metode Mengajar Guru Terhadap Prestasi Belajar Pada Siswa Kels XI Mata Pelajaran Ekonomi Sekolah Menengah Atas Muhammadiyah 1 Surakarta Tahun Ajaran 2014/2015 - Rahmawati, Erfiana Restya, Dr. Wafrotur Rohmah, MM (2015)
The purpose of this study was to determine: 1) the effect of the interest in learning to learning achievement in class XI student of economic subjects, 2) the influence of teacher's teaching methods to the learning achievement in class XI student of economic subjects, 3) the effect of learning and teaching methods of teachers to learning achievement in class XI ekonomi.Jenis subjects of this research is quantitative research associative. The population in this study were students of class XI IPS SMA Muhammadiyah 1 Surakarta, amounting to 140 students with a sample of 100 students were taken by proportional random sampling technique. Data collection techniques using questionnaires that have been tested with the validity and reliability test. The analysis technique used is multiple linear regression, t-test, F, R ^ 2 test, and the relative contribution and efektif.Berdasarkan data analysis results obtained by multiple linear regression equation as follows: Y = 2.101 + 0,018X1 + 0,012X¬2, means learning achievement is affected by the interest in learning and teaching methods teachers. Based on the analysis and discussion, it can be concluded that: (1) There is interest in studying the effect on learning achievement. This is proven by the results of the calculation tcount untukvariabel interest in learning of 4.174 so thitung> ttable or 4.174> 1.985 with a significance value of 0.000 <0.05. (2) There is the influence of teacher's teaching methods on learning achievement. This is proven by the results of the calculation of the variable tcount for teachers teaching methods by 2.158 so thitung> ttable or 2.158> 0.033 1,985dengan significance value <0.05. (3) There is the influence of learning and teaching methods of teachers on learning achievement. This is evident from the test results that obtain F Fhitung 18.057> F table (3.090) with significant value 0.000 <0.05. (4) Variable interest in studying the relative contribution of 71% and the effective contribution of 19.23%, the variable method of teaching the teacher gives the relative contribution of 29% and the effective contribution of 7.87%, so that it can be said that the interest in learning more dominant influence achievement study. (5) The calculation of the value of R2 is 0.271, meaning 27.1% of learning achievement is influenced by the interest in learning and teaching methods of teachers, while the remaining 72.9% is influenced by other factors not participate in this study. Keywords: interest in learning, teachers teaching methods, learning achievement.